2012
DOI: 10.1088/0004-6256/143/4/95
|View full text |Cite
|
Sign up to set email alerts
|

THE SUB-SATURN MASS TRANSITING PLANET HAT-P-12b

Abstract: We present new photometric data of the transiting planet HAT-P-12b observed in 2011. Our three transit curves are modelled using the JKTEBOP code and adopting the quadratic limb-darkening law. Including our measurements, 18 transit times spanning about 4.2 yr were used to determine the improved ephemeris with a transit epoch of 2,454,187.85560±0.00011 BJD and an orbital period of 3.21305961±0.00000035 d. The physical properties of the star-planet system are computed using empirical calibrations from eclipsing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
(33 reference statements)
5
26
1
Order By: Relevance
“…For the Hartman et al (2009) light curves, we achieve excellent agreement in the parameters, but find error bars that are higher by up to a factor of 2. The Lee et al (2012) results, which were also derived with JKTEBOP, are reproduced as well, however our error estimation yields values higher by a factor of 2 for the planet-to-star radius ratio and 10 for the orbital inclination. The source of this discrepancy remains unexplained.…”
Section: Re-analysis Of the Literature Datasupporting
confidence: 69%
See 2 more Smart Citations
“…For the Hartman et al (2009) light curves, we achieve excellent agreement in the parameters, but find error bars that are higher by up to a factor of 2. The Lee et al (2012) results, which were also derived with JKTEBOP, are reproduced as well, however our error estimation yields values higher by a factor of 2 for the planet-to-star radius ratio and 10 for the orbital inclination. The source of this discrepancy remains unexplained.…”
Section: Re-analysis Of the Literature Datasupporting
confidence: 69%
“…There are also a handful of examples of candidates or confirmed multiplanet systems with a hot Jupiter, where indications or evidence of another companion was achieved with the radial velocity method, see Hartman et al (2014) and references therein. Lee et al (2012) found variations in the transit times of HAT-P-12b that are significantly larger than their error values. We use our sample of transit observations to follow up on this potential TTV detection.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…A summary of the observations is listed in Table 1, where we present observing interval, numbers of nights, CCD type, field of view (FOV), and numbers of observed points. The instruments and reduction methods for the FLI IMG4301E and ARC 4K CCD cameras are the same as those described by Lee et al (2009bLee et al ( , 2012b. In order to make an optimal artificial comparison source during our observing runs, we monitored a few tens of stars imaged on the chip at the same time as the eclipsing pair.…”
Section: New Long-term Observations and Eclipse Timesmentioning
confidence: 99%
“…The observations will also be focused to check possible out-ofeclipse and color brightness variations which would indi- www.an-journal.org Lee et al (2012).…”
Section: Observing Network and First Observationsmentioning
confidence: 99%